(untitled) ("Journal "U". Economy. Management. Finance.", 2025)
Analysis of time series using statistical approaches and creation of trend models on their basis to determine the values ​​of various parameters is a common practice. The article presents the development of trend models using Microsoft Excel software. In the process of solving a specific problem, the characteristics of trend stability (standard deviation, variation coefficient and average approximation error) were determined. The results of the study allowed us to make a number of reasonable conclusions.